Pengaruh Program Seniman Masuk Sekolah terhadap Motivasi Siswa - Murcahyanto, Hary; Fahrurrozi, Muhammad; Mohzana, Mohzana (JOEAI (Journal of Education and Instruction), 2021)
ABSTRACT This study aims to analyze student motivation in music lessons. Using a multi-case study, ten state senior high schools in East Lombok Regency were selected as the research sample. This research is a qualitative study using an in-depth interview approach in which data collection, observation and analysis of related documents is applied. Data presented in a narrative. The results of the study revealed that the artists in school are significantly functional and play a role in increasing and encouraging the level of student motivation in music lessons. This research concludes that students' motivation in music is strongly influenced by the presence of practitioners or artists who are in direct contact with students, especially in the learning process at school. Keywords: Artists go to school; Motivation; Music Arts Education